2000
DOI: 10.1097/00004647-200008000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Cerebral Blood Flow and Oxygen Metabolism in Infant Pigs during Selective Brain Hypothermia

Abstract: Summary:Studies documenting the cerebral hemodynamic consequences of selective brain hypothermia (SBH) have yielded conflicting data. Therefore, the authors have studied the effect of SBH on the relation of cerebral blood flow (CBF) and CMRO 2 in the forebrain of pigs. Selective brain hypothermia was induced in seven juvenile pigs by bicarotid perfusion of the head with extracorporally cooled blood. Cooling and stepwise rewarming of the brain to a T brain of 38°C, 25°C, 30°C, and 38°C at normothermic T trunk (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 42 publications
1
33
3
Order By: Relevance
“…Animal studies suggest that, during circulatory arrest, the reduction of metabolic rate nearly parallels the decrease in CBF (22). Moreover, there is direct evidence of coupling of CBF to cerebral oxygen metabolism from swine (12,62) and dog (39) studies. However, there is also evidence of uncoupling between CBF and cerebral oxygen metabolism during deep (20 -26°C) and profound (Ͻ20°C) cooling (12,39).…”
Section: Theory and Methodsmentioning
confidence: 98%
“…Animal studies suggest that, during circulatory arrest, the reduction of metabolic rate nearly parallels the decrease in CBF (22). Moreover, there is direct evidence of coupling of CBF to cerebral oxygen metabolism from swine (12,62) and dog (39) studies. However, there is also evidence of uncoupling between CBF and cerebral oxygen metabolism during deep (20 -26°C) and profound (Ͻ20°C) cooling (12,39).…”
Section: Theory and Methodsmentioning
confidence: 98%
“…However, the oxygen consumption of most individual organs falls in response to hypothermia because of the biophysical effect of temperature on metabolic activity. The brain is no exception, as its oxygen consumption decreases 50 to 75% for every 10°C decrease in brain temperature (1,4,13). In the present study, the effect of hypothermia on fetal cerebral oxygen consumption was similar to that of previous reports in the newborn and adult, with a 1.6°C decrease in brain temperature resulting in a 25% decrease in cerebral oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In the newborn and adult, lowering cerebral oxygen consumption with either hypothermia (1,4,6) or barbiturates (2,3,5) results in commensurate decreases in cerebral oxygen delivery, with little or no change in cerebral oxygen extraction. In the present study, we observed in the fetus a similar relationship between cerebral oxygen consumption and cerebral oxygen delivery (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations